Magnetic properties of amorphous and nanoscrystalline FINEMET type iron-based alloys - Babich, M.; Zakharenko, M.; Orlenko, M. (Functional Materials, 2006)
Temperature dependences of magnetic susceptibility for rapidly quenched FINEMET
type Fе₇₃,₅Cu₁Ме₃Si₁₃,₅В₉ (Ме = Zr, Nb, Мо) amorphous alloys have been studied by Faraday technique within 300 to 900 К temperature range. The values of Curie temperature, magnetic moment per iron atom and crystallization temperature have been determined. These parameters were found to be dependent on difference of the number of d-electrons
in Fе and Ме atoms. The revealed peculiarities in paramagnetic susceptibility behavior are connected directly with the structure evolution processes in the rapidly quenched ribbons. This evolution consists in the size increasing of crystal-like inclusions of silicon solid solution in α-Fе. Magnetically, these inclusions behave as super-paramagnetic particles. Методом фарадея дослiджено температурнi залежностi магнiтної сприйнятливостi швидкoзагартованих аморфних сплавiв типу FINEMET Fе₇₃,₅Cu₁Ме₃Si₁₃,₅В₉ (Ме = Zr, Nb, Мо) в iнтервалi температур 300-900 К, визначенi їх температура кюрi, магнiтний момент на атом залiза та температура кристалiзацiї. Встановлено, що цi параметри корелюють з рiзницею d-електронiв Fе та Ме. Виявленi особливостi у поведiнцi парамагнiтної сприйнятливостi безпосередньо пов'язанi з процесами структурної еволюцiї швидкозагартованих стрiчок, що полягає у збiльшеннi розмiрiв кристалоподiбних включень твердого розчину кремнiю в α-Fе. Цi включення у магнiтному вiдношеннi поводять себе як суперпарамагнiтнi частинки. Методом Фарадея исследованы температурные зависимости магнитной восприимчивости быстрозакаленных сплавов типа FINEMET Fе₇₃,₅Cu₁Ме₃Si₁₃,₅В₉ (Ме = Zr, Nb, Мо) в интервале температур 300-900 К, определены их температура кюри, магнитный момент на атом железа и температура кристаллизации. Установлено, что эти параметры коррелируют с разностью d-электронов Fе и Ме. Обнаруженные особенности в поведении парамагнитной восприимчивости непосредственно связаны с процессами структурной эволюции быстрозакаленных лент, которая заключается в увеличении размеров кристаллоподобных включений твердого раствора кремния в a-Fе. Эти включения в магнитном отношении ведут себя как суперпарамагнитные частицы.